GGE bi-plot analysis for grain yield in chickpea (Cicer arietinum) under normal and heat stress conditions - JHA, UDAY CHAND; KOLE, PARESH CHANDRA; SINGH, NARENDRA PRATAP; SHIL, SANDIP; KUMAR, HEMANT (The Indian Journal of Agricultural Sciences, 2019)
Efficiency of genetic gain received through selection is seriously affected by genotype × environment (G×E) interaction, as G×E directly affects the stability and performance of genotype under multi environment. In the current study a total of 34 chickpea (Cicer arietinum L.) genotypes were evaluated at two locations (Kanpur and Bhopal) in two seasons (timely sown and late sown conditions) during 2016-17 to gain insights into the G × E effect and the stability of genotypes grown across the sites. Plot yield data recorded from the genotypes were analyzed by using GGE bi-plot method. The combined analysis of variance (ANOVA) revealed highly significant effects of environment on plot yield attribute among the genotypes, evaluated over the two seasons across the two locations. However, the most stable genotype across the two locations remained g 23 (JAKI 9218). Among the tested environments Bhopal timely sown (BL-T) and Bhopal late sown (BL-L) were the most representative, whereas Kanpur timely sown (KAN-T) was the least representative. Moreover, g 01 (HC 1) was the best cultivar under KAN-T and KAN-L environments whereas, g 23 (JAKI 9218) was the best cultivar under BL-T and BL-L environments.